ANALISIS KEBIJAKAN HUKUM PIDANA TERHADAP WARGA NEGARA ASING PELAKU TINDAK PIDANA NARKOTIKA - Keke Wismana Purba; Muhammad Hamdan; Mahmud Mulyadi; Edy Ikhsan (USU LAW JOURNAL, 2016)
ABSTRACT Application of criminal law policies against narcotics crimes in one country implemented based on the principle of the territory operates a place (locus delicti) as the basis for the enforcement of the law. The application of the sanctions law against citizens of the society including foreign nationals who break the law, expected to be positive for the development of the personality of the influential community. Implementation of the policy of criminal law in particular criminal dead is currently subject to a Presidential Determination No. 2 of 1964 On The implementation of the Criminal to death determined by the courts In General and military Judicial environment. Barriers of pre and post implementation of the policy of criminal law in particular criminal foreign nationals dead to the perpetrators of the crime of narcotics, namely the existence of a difference of understanding of the concept of the the policy of criminal law, pros cons among the public, academics, legal practitioners and law enforcers linked the implementation of the policy of criminal law in particular criminal foreign nationals dead to the perpetrators of the crime of narcotics, as well as the intervention of various countries linked the implementation of the policy of criminal law. Keywords: Criminal Law, Criminal Policy Dead, Foreign Citizens